A nonplanar slow rupture episode during the 2000 Miyakejima dike intrusion. Issue 3 (4th March 2017) - Cattania, Camilla; Rivalta, Eleonora; Hainzl, Sebastian; Passarelli, Luigi; Aoki, Yosuke
Abstract: Magmatic intrusions release extensional strain in the Earth's crust upon availability of magma. Intrusions are typically accompanied by earthquake swarms and by surface faulting that is often larger than what is expected from the magnitude of the induced earthquakes. The 2000 Miyakejima dike intrusion triggered the largest volcanic earthquake swarm monitored so far, with five M l >6 earthquakes. We analyze the seismicity and deformation induced by the Miyakejima dike with the aim of constraining the timescale and mechanisms of slow strain release during the episode. In six earthquake bursts lasting few hours and migrating at ∼1 km h −1 we find candidates for slow earthquakes. Each burst nucleated at the tips of previous bursts, suggesting stress interaction. The variability of fault plane solutions indicates that the bursts occurred on a complex system of fractures, consistent with weakly consolidated surface layers strained by spatially inhomogneous stresses that change in time, such as those induced by a dike. Based on dislocation models, we find that deformation is best explained by aseismic slip (in addition to the seismic burst), with a moment 1.3 to 2.3 times larger than the earthquakes' seismic moment, and opening of 0.20 ± 0.07 m on the dike. The aseismic slip occurred over a few hours, with moment, duration, and migration velocity consistent with that of previously observed slow slip events. We argue that the seismic bursts are likely driven by slow slip, sharing most properties with tectonic slow slip events and swarms, but occurring on a set of nonaligned faults. Key Points: During the 2000 Miyakejima dike intrusion we detect short bursts of seismicity lasting a few hours and propagating along the dike The surface deformation during the largest burst is best explained by aseismic slip taking place on the same faults as the earthquakes Intermittent slip episodes with a large aseismic component may accommodate a significant fraction of strain during diking